2016
DOI: 10.1007/s10661-016-5247-x
|View full text |Cite
|
Sign up to set email alerts
|

Phytostabilization of arsenic in soils with plants of the genus Atriplex established in situ in the Atacama Desert

Abstract: In the ChiuChiu village (Atacama Desert, Chile), there is a high concentration of arsenic (As) in the soil due to natural causes related to the presence of volcanoes and geothermal activity. To compare the levels of As and the growth parameters among plants of the same genus, three species of plants were established in situ: Atriplex atacamensis (native of Chile), Atriplex halimus, and Atriplex nummularia. These soils have an As concentration of 131.2 ± 10.4 mg kg(-1), a pH of 8.6 ± 0.1, and an electrical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The treatments during the rainy season, in all the areas, showed higher values for soil moisture ( Figure 1C), but no variations were noted between treatments in the dry season. The high values identified for the pH and electrical conductivity were close to the characteristic values reported for arid regions (FERNÁNDEZ et al, 2016). Figure 1 -Soil analysis of the experimental areas during the dry and rainy seasons: 1: 1 stratum electrical conductivity (50 g soil / 50 ml distilled water) (A); stratum pH 1: 2.5 (10 g soil / 25 ml distilled water) (B); soil moisture (C).…”
Section: Resultssupporting
confidence: 77%
“…The treatments during the rainy season, in all the areas, showed higher values for soil moisture ( Figure 1C), but no variations were noted between treatments in the dry season. The high values identified for the pH and electrical conductivity were close to the characteristic values reported for arid regions (FERNÁNDEZ et al, 2016). Figure 1 -Soil analysis of the experimental areas during the dry and rainy seasons: 1: 1 stratum electrical conductivity (50 g soil / 50 ml distilled water) (A); stratum pH 1: 2.5 (10 g soil / 25 ml distilled water) (B); soil moisture (C).…”
Section: Resultssupporting
confidence: 77%
“…The surficial mineralogy of the IKMHSS tailings is dominated by high iron and sulfur content with the major contaminant of concern being arsenic (ca. 2100 mmol kg –1 Fe, 3100 mmol kg –1 S, and 40 mmol kg –1 As). , Under the oxidizing conditions of the surficial IKMHSS tailings, ferrous sulfides naturally weather to form ferric (oxyhydr)­oxides and (hydroxy)­sulfates. , These arsenic enriched secondary minerals have the potential for off-site transport as geo-dust in wind-driven erosion. One potential low-cost, long-term remediation method proposed for such abandoned mine tailings involves phytostabilization, i.e., the establishment of a sustainable vegetation “cap” with which to effectively contain legacy tailings particles and the associated metal­(loid)­s including arsenic, thereby diminishing contaminant exposure to adjacent communities. Compost-assisted direct planting during tailings phytostabilization has the goals of immobilizing contaminants against leaching or off-site particulate transport, establishing a positive feedback to improved soil health and fertility while decreasing contaminant leaching to groundwater. , However, the changes in metal­(loid) speciation that occur as a result of root proliferation in the porous tailings media, and that control stabilization at the molecular scale, remain poorly resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The plants must also be easy to grow and quickly form a dense canopy and root system [82]. Fernández et al [83] showed that three plants, Atriplex atacamensis, Atriplex halimus, and Atriplex nummularia, accumulated higher As concentrations in their roots than in their shoots, confirming the suitability of the plants for phytostabilisation.…”
Section: The Concept Of Phytoremediationmentioning
confidence: 99%